A Software Model and Specification Language for Non-WIMP User Interfaces. - Jacob, Robert J. K.; Deligiannidis, Leonidas.; Morrison, Stephen. (Tufts University. Tisch Library., 2017)
We present a software model and language for describing and programming the fine-grained aspects of interaction in a non-WIMP user interface, such as a virtual environment. Our approach is based on our view that the essence of a non-WIMP dialogue is a set of continuous relationships—most of which are temporary. The model combines a data-flow or constraint-like component for the continuous relationships with an event-based component for discrete interactions, which can enable or diable individual continuous relationships. To demonstrate our approach, we present the PMIW user interface management system for non-WIMP interactions, a set of examples running under it, a visual editor for our user interface description language, and a discussion of our implemantation and our restricted use of constraints for a performance-driven interactive situation. Our goal is to provide a model and language that captures the formal structure of non-WIMP interactions in the way that various previous techniques have captured command-based, textual, and event-based styles and to suggest that using it need and not compromise real-time performance.